Potential of manure based biogas to replace conventional and non-conventional fuels in India. Issue 1 (12th January 2015) - Nautiyal, Sunil; Goswami, Mrinalini; Manasi, S.; Bez, Prasanta; Bhaskar, K.; Khan, Y.D. Imran
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the potential of biogas in India for energy conservation and its potential in emission reduction through proper manure management and utilizing the tappable droppings while replacing the conventional and non-conventional fuel. Design/methodology/approach – The authors have looked at the production, use and tappability of animal excreta for possible biogas generation and reduction in fuelwood consumption on one hand and emission reduction across the Indian states on the other. The average percentage of Biogas potential is created in the GIS database for analyzing the data set in the spatial domain using ArcGIS 9.2 software. Findings – The paper examines that unused manure contributes to the greenhouse gas (GHG) and has huge potential of reducing the emission through proper utilization across the Indian states. Keeping current climate change dilemma in view this could be one of the feasible options to cope with the climate change and mitigating the threats. Research limitations/implications – A comprehensive data regarding methane emission from various sources is not readily available so far. With the help of this research work the authentic data has been collected from different government departments' data banks and past research work. However, the authors have limited to few conversion aspects in quantifying the emission factor due to complexity of the various data sets. Practical implications – Looking at the availability of usable animal excreta in different climatic regions, the attempt has been made in demarcating economically viable and technically feasible areas for biogas generation in India. An environmental and economic cost benefit analysis for adopting this renewable energy source has also been incorporated within this research. Originality/value – The paper examined the GHG contribution of unused manure and the possibility of reducing it through proper utilization. The adverse environmental consequences of the use of conventional and non-conventional cooking fuels have also been analyzed in terms of GHG emissions. The same was assessed for the whole lifecycle of liquefied petroleum gas, which is commonly assumed as a clean fuel.